DEPRESSIVE SYMPTOMS AND CHRONIC DISEASE: IS THERE AN ASSOCIATION FOR OLDER AFRICAN AMERICANS?. (11th November 2018) - Cho, S; Hamler, T
Abstract: The purpose of this study was to identify the association between physical health problems and depressive symptoms among older African Americans (age > 65) using the 2014 Health and Retirement Study (N = 1, 206). Membership in a racial/ethnic minority group may restrict access to mental health services. Many existing studies have reported the higher prevalence of depressive symptoms among older minority populations. Racial/ethnic minority groups, particularly African Americans experience a disproportionate burden of chronic conditions, as well as disparities accessing health care and preventive services due to a variety of socioeconomic, behavioral, and other factors. For statistical analysis, depressive symptoms were measured with eight-item CES-D Scale (M = 1.546, SD = 1.952), and chronic health conditions were measured by asking whether respondents had ever diagnosed with the following seven diseases: high blood pressure, diabetes, cancer, lung disease, heart disease, stroke, and arthritis (M = 2.736, SD = 1.285). Sociodemographic covariates included self-reported health, age, gender, income (logged), marital status, and educational attainment. An OLS regression showed that older African Americans having one additional chronic health problem was associated with .133 higher depressive symptoms after controlling for the covariates (p = .002). The regression model could be an appropriate prediction on depressive symptoms, Adjusted R-square = .161, F (7, 1, 198) = 34.127, p < .001. Depression and chronic illness together are drivers that increase healthcare costs and have developed into a critical problem for an already vulnerable older African American population, requiring a critical attention from both practice and policy.